2020
DOI: 10.1039/d0ra04090h
|View full text |Cite
|
Sign up to set email alerts
|

Mussel inspired ZIF8 microcarriers: a new approach for large-scale production of stem cells

Abstract: Mussel inspired ZIF8 microcarriers with high surface area, biocompatibility, and nanoscale surface roughness are applied to enhance mesenchymal stem cell attachment and proliferation in 3D cell culture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…This may indicate the ability to deliver growth factors that assist the regeneration of chondrocytes, such as TGF-β1, through similar methods. Another study by Fardjahromi et al (2020) has shown the ability to use polystyrene beads that are immobilized with PDA, polyethyleneimine, and ZIF-8 for culturing hADSCs [ 51 ]. This allows the stem cells to adhere and proliferate, which may ultimately be used as a source for differentiating into chondrocytes for cartilage regeneration.…”
Section: Factors To Consider When Designing An Ideal Composite For Oa...mentioning
confidence: 99%
“…This may indicate the ability to deliver growth factors that assist the regeneration of chondrocytes, such as TGF-β1, through similar methods. Another study by Fardjahromi et al (2020) has shown the ability to use polystyrene beads that are immobilized with PDA, polyethyleneimine, and ZIF-8 for culturing hADSCs [ 51 ]. This allows the stem cells to adhere and proliferate, which may ultimately be used as a source for differentiating into chondrocytes for cartilage regeneration.…”
Section: Factors To Consider When Designing An Ideal Composite For Oa...mentioning
confidence: 99%
“…The level of autocrine cell fate determination markers in the ZIF-8 modified polypropylene membrane was also raised. When compared to the tissue culture plate, osteogenic markers were clearly overexpressed in response to ZIF-8 layer biomechanical features ( Asadniaye Fardjahromi et al, 2020 ; Ejeian et al, 2020 ). The nanoscale ZIF-8 coating on porous titanium implants increases osteogenic-related gene expression and protein secretion, as well as extracellular matrix mineralization, osteoblastic activity, and bone regeneration ( Chen et al, 2017 ).…”
Section: Applications Of Zeolites In Bone Tissue Engineeringmentioning
confidence: 99%
“…[12,13] However, most of the metal-based catalysts were heterogeneous catalysts, the catalytic activity of some of these decreases upon immobilization due to the reduction in accessibility of active sites. [14] Furthermore, these heterogeneous systems typically operate under harsh conditions, such as high temperature to achieve high yields. [15,16] Among numerous transition metal-based catalysts, the polyoxometalate catalysts have attracted wide attention due to their excellent catalytic activity [17,18] and easy adjustment of acid or redox properties.…”
Section: Introductionmentioning
confidence: 99%